Respiration of Bloodstream Forms of the Parasite Trypanosoma brucei brucei Is Dependent on a Plant-like Alternative Oxidase - Clarkson, A B C; Bienen, E.J.; Pollakis, G; Grady, R.W. (Elsevier, 1989)
CoQ links the sn-glycerol-3-phosphate dehydrogenase and oxidase components of the cyanide-insensitive, non-cytochrome-mediated respiratory system of bloodstream African trypanosomes. In this and other characteristics, their respiratory system is similar to the alternative oxidase of plants. The parasites contain 206 ng of CoQ9 mg protein−1 which co-sediments with respiratory activity. The redox state of this CoQ responds in a manner consistent with respiratory function: 60% being in the reduced form when substrate is available and the oxidase is blocked; 13% being in the reduced form when the oxidase is functioning and there is no substrate. The addition of CoQ to aceton-extracted cells stimulates salicylhydroxamic acid-sensitive respiration by 56%. After inhibition of respiration by digitonin-mediated dispersal of the electron transport components, liposomes restore 40% of respiratory activity while liposomes containing CoQ restore 66% of this activity. A less hydrophobic analogue, reduced decyl CoQ, serves as a direct substrate for the trypanosome oxidase supporting full salicylhydroxamic acid-sensitive respiration. After digitonin disruption of electron transport, the nonreduced form of this synthetic substrate can reestablish the chain by accepting electrons from dispersed sn-glycerol-3-phosphate dehydrogenase and transferring them to the dispersed oxidase. Similarities between the alternative oxidase of plants and the oxidase of the trypanosome respiratory system include: mitochondrial location, lack of oxidative phosphorylation, linkage of a dehydrogenase and an oxidase by CoQ, lack of sensitivity to a range of mitochondrial inhibotors, and sensitivity to a spectrum of inhibitors which selectively block transfer of electrons from reduced CoQ to the terminal oxidase but do not block electron transfer to the cytochrome bc1 complex of the mammalian cytochrome chain.